Men's Mental Health: Social Determinants and Implications for Services. (September 2018) - Affleck, William; Carmichael, Victoria; Whitley, Rob
Numerous scholars have stated that there is a silent crisis in men's mental health. In this article, we aim to provide an overview of core issues in the field of men's mental health, including a discussion of key social determinants as well as implications for mental health services. Firstly, we review the basic epidemiology of mental disorders with a high incidence and prevalence in men, including suicide and substance use disorder. Secondly, we examine controversies around the low reported rates of depression in men, discussing possible measurement and reporting biases. Thirdly, we explore common risk factors and social determinants that may explain higher rates of certain mental health outcomes in men. This includes a discussion of 1) occupational and employment issues; 2) family issues and divorce; 3) adverse childhood experience; and 4) other life transitions, notably parenthood. Fourthly, we document and analyze low rates of mental health service utilization in men. This includes a consideration of the role of dominant notions of masculinity (such as stubbornness and self-reliance) in deterring service utilization. Fifthly, we note that some discourse on the role of masculinity contains much "victim blaming, " often adopting a reproachful deficit-based model. We argue that this can deflect attention away from social determinants as well as issues within the mental health system, such as claims that it is "feminized" and unresponsive to men's needs. We conclude by calling for a multipronged public health–inspired approach to improve men's mental health, involving concerted action at the individual, health services, and societal levels.